2009
DOI: 10.1093/jxb/erp193
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast anchoring: its implications for the regulation of intracellular chloroplast distribution

Abstract: The intracellular distribution of organelles plays a pivotal role in the maintenance and adaptation of a wide spectrum of cellular activities in plants. Chloroplasts are a special type of organelle able to photosynthesize, capturing light energy to fix atmospheric CO2. Consequently, the intracellular positioning of chloroplasts is crucial for plant growth and development. Knowledge of the photoreceptors and cellular apparatus responsible for chloroplast movement has gradually accumulated over time, yet recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…The actin cytoskeleton is a network of individual, cross-linked, and/or highly bundled filamentous structures. In plant cells, these continuously remodeled arrays power intracellular locomotion and serve as "cellular motorways" for the transport of various organellar cargos [47]. Actin filaments are also implicated in vesicle trafficking between endomembrane compartments, especially in trafficking to and from the plasma membrane [48].…”
Section: Discussionmentioning
confidence: 99%
“…The actin cytoskeleton is a network of individual, cross-linked, and/or highly bundled filamentous structures. In plant cells, these continuously remodeled arrays power intracellular locomotion and serve as "cellular motorways" for the transport of various organellar cargos [47]. Actin filaments are also implicated in vesicle trafficking between endomembrane compartments, especially in trafficking to and from the plasma membrane [48].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that in plants the intracellular mobility and positioning of chloroplasts depend on microfilament-and microtubule-based cytoskeletons (Dong et al, 1998;Sato et al, 2001;Shimmen and Yokota, 2004;Wada and Suetsugu, 2004;Chuong et al, 2006;Paves and Truve, 2007;Reisen and Hanson, 2007;Takagi et al, 2009). Close links of chloroplasts with actin filaments were shown in vascular plants and algae (Takagi, 2003).…”
Section: The Pten Domain Mediates the Association Of Fh5 With Chloropmentioning
confidence: 99%
“…As with most organelle movements in plants, the actin cytoskeleton also plays an important role in determining the intracellular positioning of chloroplasts and in directional chloroplast photorelocation movements (Oikawa et al, 2003;Kadota et al, 2009;Takagi et al, 2009;Suetsugu et al, 2010b). It has recently been reported that short chloroplast-actin (cp-actin) filaments are essential for chloroplast movements (Kadota et al, 2009;Kodama et al, 2010;Suetsugu et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%